Digital Circular School in Islamic Education: A PRISMA Based Systematic Literature Review (2020-2025) and an Integrative Conceptual Model of Islamic Values, Circularity, and Digital Capacity - Murdiyanto, Murdiyanto; Susetyarini, Eko; Cholily, Yus Mochamad; Syaifuddin, Mohammad (Jurnal Pendidikan Islam, 2025)
Purpose – This study formulates a management framework for pesantren, madrasah, and Islamic schools to respond to the fragmentation of digitalization practices and ecological sustainability through an integrative Digital Circular School model that coherently links Islamic values, circularity, and digital capacity Design/methods/approach – The study uses a conceptual design based on a systematic literature review with a PRISMA flow. The search was conducted in Scopus, Google Scholar, and DOAJ for publications from 2020 to 2025 using keywords related to circular school, circular economy, eco-pesantren, digital Islamic school management, and Islamic values. Selected articles were analyzed through thematic analysis (theoretical reduction, thematic categorization, and integrative synthesis) to build a conceptual model Findings – Of 412 initial records, 198 remained after duplicate removal and administrative screening, 74 passed title and abstract screening, and 27 publications met the eligibility criteria. The literature is dominated by literature studies (55 percent) and qualitative case studies (25 percent). The synthesis identifies four themes: integration of Islamic curriculum and pedagogy with technology, digital Islamic leadership and governance, adoption of key technologies along with ethical challenges, and character formation and spirituality in the digital space. These findings produce a cyclical model with three pillars: reinforcement of Islamic values, enhancement of circularity practices, and expansion of digital capacity; this model is conceptual and has not been empirically tested. Research implications – The model can serve as an initial guide to design digital governance based on amanah and accountability, mainstream paperless practices, 3R, energy efficiency, and resource monitoring through information systems and dashboards; while also strengthening digital literacy, ecological literacy, and Islamic character development within the curriculum and school culture.